Total Hip Arthroplasty in Sanglah General Hospital Denpasar, January 2013 – July 2016 : a Cross-Sectional Study - I Gusti Kadek Satrio Adiwardhana; I Gusti Ngurah Bagus Andhika Pramana (Cermin Dunia Kedokteran, 2018)
Background: Total Hip Arthroplasty (THA) is one of the most frequent elective surgeries in orthopaedics and traumatology. Patient characteristics are important predictors for a successful treatment. Objectives: To provide descriptive data on THA patients’ characteristics in Sanglah General Hospital, January 2013 - July 2016. Methods: A cross sectional descriptive study of THA cases at Sanglah General Hospital from January 2013 to July 2016. The data obtained included sex, age, diagnosis, arthroplasty type, comorbid, ASA status, duration of operation, and postoperative care. Results: There were 45 patients, mostly women (67.6%), average age of 55.6 ± 11.4 years, osteoarthritis as the major diagnosis (42,22%), hypertension as the most frequent comorbid (37,8%), and most patients had arthroplasty procedure with uncemented fixation. Conclusion: Patient characteristics and THA procedures have similarities with many studies in different countries.Latar Belakang: Total hip arthroplasty (THA) adalah salah satu operasi elektif yang sering dilakukan di bidang orthopaedi dan traumatologi. Karakteristik pasien merupakan prediktor penting untuk keberhasilan terapi. Tujuan: Data deskriptif berdasarkan karakteristik pasien THA di Rumah Sakit Umum Pusat Sanglah Januari 2013-Juli 2016. Metode: Studi deskriptif cross sectional kasus total hip arthroplasty (THA) elektif di Rumah Sakit Umum Pusat Sanglah periode Januari 2013 - Juli 2016. Data yang dianalisis meliputi jenis kelamin, usia, diagnosis, tipe arthroplasty, komorbiditas, status ASA, durasi operasi, dan perawatan pasca operasi. Hasil: Didapatkan 45 pasien, kebanyakan wanita (67.6%), dengan rerata usia 55.6 ± 11.4 tahun, diagnosis utama osteoarthritis, penyakit komorbid hipertensi, dan tindakan arthroplasty dengan metode fiksasi cementless. Simpulan : Karakteristik pasien dan prosedur THA memiliki kesamaan dengan kebanyakan studi lain di berbagai negara.